2009
DOI: 10.1063/1.3096712
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Turbulent equipartition theory of toroidal momentum pinch” [Phys. Plasmas 15, 055902 (2008)]

Abstract: The comment addresses questions raised on the derivation of the momentum pinch velocity due to the Coriolis drift effect [A. G. Peeters et al., Phys. Rev. Lett. 98, 265003 (2007)]. These concern the definition of the gradient, and the scaling with the density gradient length. It will be shown that the turbulent equipartition mechanism is included within the derivation using the Coriolis drift, with the density gradient scaling being the consequence of drift terms not considered in [T. S. Hahm et al., Phys. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Table I summarizes the main difference between our papers and their letter. Finally, the comment of Peeters et al 6 contains an incorrect description of our TEP theory for the momentum pinch, stating that "Hahm et al assume mixing of the toroidal angular momentum," while we did not.…”
Section: Main Difference Between Our Papers and Their Lettermentioning
confidence: 99%
See 1 more Smart Citation
“…Table I summarizes the main difference between our papers and their letter. Finally, the comment of Peeters et al 6 contains an incorrect description of our TEP theory for the momentum pinch, stating that "Hahm et al assume mixing of the toroidal angular momentum," while we did not.…”
Section: Main Difference Between Our Papers and Their Lettermentioning
confidence: 99%
“…With these differences in approaches, emphases, and also in ensuing approximations, there have been some misunderstandings and improper interpretations of our work and their own work in their comment. 6 The comment by Peeters et al, 6 contains the following claims with which we disagree based on technical grounds:…”
Section: Introductionmentioning
confidence: 99%
“…The same fluxes have, however, recently been derived from a fluid formulation in [10]. They are divided into Turbulent [8,41] (3) and thermodiffusion (4) The magnetic drift frequency has here been averaged over the mode profile as indicated by the bar in ω Di . Moreover <k || > has been averaged over the radial mode profile.…”
Section: Time Dependent Fluid Modellingmentioning
confidence: 99%
“…[8]. Obviously, the calculated radial fluxes should be frame independent and it can be shown that the TEP contribution is incorporated in the description that uses the Coriolis drift (see [41]). …”
Section: Theoretical Predictions Of Toroidal Momentum Transport From mentioning
confidence: 99%
“…The comment by Peeters et al, 6 contains the following claims with which we disagree based on technical grounds:…”
mentioning
confidence: 96%